Implementation of Anesthesia Management Care (ASKAN) in Pre-Regional Anesthesia - Maharyawan, I Wayan Agus; Lewar, Emanuel Ileatan (Indonesian Journal of Global Health Research, 2024)
Anesthesia administrators have the main duties in the anesthesia management care service (ASKAN) which includes pre-, intra- and post-anesthesia anesthesia services. Knowledge about writing anesthesia is still lacking. Insufficient knowledge will impact patient satisfaction. The implementation of ASKAN still has different understandings between fellow anesthesia administrators in the implementation of anesthesia management care. This study aims to find out how ASKAN is implemented in pre-regional anesthesia patients. So it can be used as material to set ASKAN standards for regional anesthesia patients. This research uses a qualitative descriptive method with a focus group discussion (FGD) approach. There were 7 participants in this study who met the inclusion criteria. Sample selection was carried out using the total sampling carried outwith zoom media. Researchers act as measuring tools and ask semi-structured questions. Analysis of this research data uses Content Analysis. The recording results were typed and analyzed using an inductive thematic approach which was then systematically identified throughout the data set. The assessment carried out during regional anesthesia is a history of the disease with AMPLE, a physical examination that focuses on the spine and extremities. Apart from focusing on regional anesthesia, the anesthetist also reviews general anesthesia preparations such as LEMONS, MOANS. Psychological preparation of the patient before surgery and physical preparation of the patient such as meeting hemodynamics is a priority so that problems do not occur during intra-anesthesia. Anesthetic problems that often arise during regional anesthesia are cardiovascular problems, anxiety, pain, nausea and vomiting. The results of this research can be used by other people, especially the anesthesia management profession, as a guide for providing anesthesia management care in regional anesthesia procedures.